Utilização da AHP e controle estatístico do processo na avaliação de módulos de irrigação por gotejamento - Reisdörfer, Marcelo (2013)
This paper shows the studied results of uniformity evaluation in 23 irrigation modules tracked by gravity in familiar farms in Salto do Lontra city / PR from 2009 to 2013. Uniformity coefficients (UC, UD, UE and ) and CEP plus the decision support AHP method were applied in this trial in order to evaluate the whole drip irrigation project. The results obtained by the uniformity coefficients indicated that the irrigation modules remained stable during the studied period. There was no significant variation from one period to another, with values of 85 and 86% for UC, so that for UD the answers were 78 and 80%; for UE, the results were 57 to 59% and for , the values ranged from 0.19 to 0.17. The Shewhart charts for individual measures, concerning the statistical control of the process, could show the special causes at each point. While, the and indices indicated that the irrigation modules met the quality control specifications and were considered "acceptable" and centralized by Montgomery requirements (2004). Regarding the use of multicriteria decision support method AHP (Analysis Hierarchic Process), it proved to be effective during the evaluation of irrigation projects. It weighted different criteria according to the perspective of a project classification as "Excellent", "Good", "Fair" and "Poor". Thus, in this trial, the AHP method rated as "excellent" the irrigation project, which was implemented in Salto do Lontra city/ PR based on both analyzed periods, whose values of consistency ratio (CR) were 0 and 0.02 from 2009 to 2010 and from 2011 to 2013